Trans-Cinnamaldehyde and Eugenol Increase Acinetobacter baumannii Sensitivity to Beta-Lactam Antibiotics - Karumathil, Deepti P.; Nair, Meera Surendran; Gaffney, James; Kollanoor-Johny, Anup; Venkitanarayanan, Kumar (Frontiers in Microbiology, 2018)
Multi-drug resistant (MDR) Acinetobacter baumannii is a major nosocomial pathogen causing a wide range of clinical conditions with significant mortality rates. A. baumannii strains are equipped with a multitude of antibiotic resistance mechanisms, rendering them resistant to most of the currently available antibiotics. Thus, there is a critical need to explore novel strategies for controlling antibiotic resistance in A. baumannii. This study investigated the efficacy of two food-grade, plant-derived antimicrobials (PDAs), namely trans-cinnamaldehyde (TC) and eugenol (EG) in decreasing A. baumannii’s resistance to seven β-lactam antibiotics, including ampicillin, methicillin, meropenem, penicillin, aztreonam, amoxicillin, and piperacillin. Two MDR A. baumannii isolates (ATCC 17978 and AB 251847) were separately cultured in tryptic soy broth (∼6 log CFU/ml) containing the minimum inhibitory concentration (MIC) of TC or EG with or without the MIC of each antibiotic at 37°C for 18 h. A. baumannii strains not exposed to the PDAs or antibiotics served as controls. Following incubation, A. baumannii counts were determined by broth dilution assay. In addition, the effect of PDAs on the permeability of outer membrane and efflux pumps in A. baumannii was measured. Further, the effect of TC and EG on the expression of A. baumannii genes encoding resistance to β-lactam antibiotics (blaP), efflux pumps (adeABC), and multi-drug resistant protein (mdrp) was studied using real-time quantitative PCR (RT-qPCR). The experiment was replicated three times with duplicate samples of each treatment and control. The results from broth dilution assay indicated that both TC and EG in combination with antibiotics increased the sensitivity of A. baumannii to all the tested antibiotics (P < 0.05). The two PDAs inhibited the function of A. baumannii efflux pump, (AdeABC), but did not increase the permeability of its outer membrane. Moreover, RT-qPCR data revealed that TC and EG down-regulated the expression of majority of the genes associated with β-lactam antibiotic resistance, especially blaP and adeABC (P < 0.05). The results suggest that TC and EG could potentially be used along with β-lactam antibiotics for controlling MDR A. baumannii infections; however, their clinical significance needs to be determined using in vivo studies.